The light in the forest eaudiobook - Richter, Conrad (Light in the Forest, 1992)
"True Son's heart felt like a stone. How could this fantastic and inferior figure in a long fawn-colored garment like a woman's be possibly anything to him-this pallid creature who revealed his feelings in front of all! In the boy's mind came the picture of his Indian father. How differently he would have looked and acted. With what dignity and restraint he could conduct himself in any situation, in peace or war, in council or the hunt, with pipe or tomahawk, rifle or scalping knife. This weak and pale-skinned man was nothing beside him 'He's not my father,' he said."-from The Light in the Forest. Johnny Butler was just four years old when his Lenni Lenape "father," Cuyloga, spoke the words that siphoned out his white blood and put Indian blood in its place. Now the Yengwes, the white soldiers, were taking him back to his "true" home. Inside of him hate and anger spread like poisons. The Light in the Forest, by Pulitzer Prize-winning author Conrad Richter, will touch a new generation with its lasting truths.